Biological Aspects of Channa limbata (Cuvier, 1831) in Ta Bo - Huai Yai Wildlife Sanctuary, Phetchabun Province, Thailand - Kan Khoomsab,; Suwit Wannasri, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The biological aspects of Channa limbata were studied between November 2013 and October 2014. A total of 346 fish specimens, 185 male and 161 female, were collected from Ta Bo, Huai Yai Wildlife Sanctuary, Phetchabun Province, Thailand. Specimens range from 7.3 - 17.2 cm in length with body weight 8 - 31 g; sex ratio between males and females was 1: 0.7. The length (L), weight (W) relationship for mixed sexes was W = 0.2064 L1.85 (R2=0.90). Gonadosomatic indices for males and females were measured monthly and varied from 0.21 - 0.65% and 1.96 - 3.74%, respectively. Condition factors for males and females ranged between 0.54 - 2.20 and 0.58 - 2.72, respectively, with fecundity range 956 to 4,652 eggs in females. Fecundity (F) to weight relationship was F = 189.53 W0.59 (R2 = 0.71) and fecundity to length relationship was F = 68.82 L1.15 (R2 = 0.77). The ratio between the intestine length and total length was 1:2, indicating that C. limbata was a carnivorous feeder. Analysis of the stomach contents gave 84% insects and 16% aquatic weed. These results can be applied to conserve efforts to prevent the extinction of C. limbata in protected areas.